Hyaluronic acid-based nanoplatforms for Doxorubicin: A review of stimuli-responsive carriers, co-delivery and resistance suppression - Ashrafizadeh, Milad (Elsevier Ltd, 2022)
10.1016/j.carbpol.2021.118491